# 1L=ML

## Simple and best practice solution for 1L=ML equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 1L=ML equation:

Simplifying
1L = ML
Solving
1L = LM
Solving for variable 'L'.
Move all terms containing L to the left, all other terms to the right.
Add '-1LM' to each side of the equation.
1L + -1LM = LM + -1LM
Combine like terms: LM + -1LM = 0
1L + -1LM = 0
Factor out the Greatest Common Factor (GCF), 'L'.
L(1 + -1M) = 0
Subproblem 1Set the factor 'L' equal to zero and attempt to solve:
Simplifying
L = 0
Solving
L = 0
Move all terms containing L to the left, all other terms to the right.
Simplifying
L = 0
Subproblem 2Set the factor '(1 + -1M)' equal to zero and attempt to solve:
Simplifying
1 + -1M = 0
Solving
1 + -1M = 0
Move all terms containing L to the left, all other terms to the right.
Add '-1' to each side of the equation.
1 + -1 + -1M = 0 + -1
Combine like terms: 1 + -1 = 0
0 + -1M = 0 + -1
-1M = 0 + -1
Combine like terms: 0 + -1 = -1
-1M = -1
Add 'M' to each side of the equation.
-1M + M = -1 + M
Combine like terms: -1M + M = 0
0 = -1 + M
Simplifying
0 = -1 + M
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.SolutionL = {0}`